Performance evaluation of an electronically controlled tractor-operated applicator for liquid urea application - DHANGER, PARVEEN; KHURANA, ROHINISH; DIXIT, ANOOP KUMAR; SINGH, MANJEET; MAHAL, AMRIT KAUR (The Indian Journal of Agricultural Sciences, 2023)
Currently, granular urea (most commonly used fertilizer) is applied through broadcasting by farmers in the field. Granular urea causes significant losses due to slower soil mineralization rates, as well as ammonia volatilization and immobilization. Hence, fertilizing crops is becoming an increasingly difficult task due to low use efficiency and in mulch field conditions, it becomes more severe. The research done on mechatronic systems of applying liquid fertilizer by spot injection in field is limited. In the present study, the performance of the developed tractor operated liquid urea applicator consisting of electronic metering mechanism was evaluated at the Research Farm of Punjab Agricultural University, Ludhiana, Punjab during 2020–22. Research was done at two different types of soil (S1: sandy loam, and S2: loam) for three different forward speeds (3.6, 2.7, 1.8 km/h). Results obtained from experiments indicated that both soil type and forward speed had a significant (P<0.05) effect on the application rate of liquid urea. The best results were obtained without affecting crop yield at a forward speed of the machine 2.7 km/h with the application rate of 1090.85 litre/ha and 1035.18 litre/ha, fuel consumption 4.13 litre/h and 4.02 litre/h and crop yield 39.50 q/ha and 39.63 q/ha, for soil type S1 and S2 respectively. The cost of operation of machine was found 1996.53 `/ha. Developed tractor operated liquid urea applicator would help in improving conventional practices which are not aligned with environmental protection (e.g. gaseous emissions and nutrient losses) and boost the adoption rate of mechanized fertigation in the crops.